2014
DOI: 10.1111/jace.12921
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Concept of Crystal Structure Applied to the Thermal Transformation of α‐C2SH

Abstract: A single crystal of a-Ca 2 [HSiO 4 ](OH) (a-C 2 SH) was repeatedly imaged at room temperature with synchrotron mid-infrared microscopy after heating to 310°C, 340°C, 370°C, and 400°C respectively. The mechanisms of the observed phase transformations are discussed on the basis of a modular concept of the crystal structures. All images show domains of dellaite, Ca 6 [Si 2 O 7 ][SiO 4 ](OH) 2 , which are predominantly formed in the core of the crystal. In the crystal rim area a-C 2 SH persists in higher abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Compositional changes in the silicate matrix due to the presence of H 2 O during the hydration/dehydration tests at 450/550ºC were observed by XRD. These changes are consistent with the hydration of Ca 2 SiO 4 to form different hydrated silicates (Garbev et al 2014;Mitsuda et al 1985;Roßkopf et al 2015;Speakman et al 1967;Yanagisawa et al 2006), being Ca 5 (SiO 4 ) 2 (OH) 2 the main compound identified in our samples (Criado et al 2015). Although these hydrated silicates only represent a small fraction of the total amount of silicates present in the composite material, the formation of these hydrates could play a role in the deterioration of the mechanical properties over cycling.…”
Section: Observations On the Decay Of Crushing Strengthsupporting
confidence: 90%
“…Compositional changes in the silicate matrix due to the presence of H 2 O during the hydration/dehydration tests at 450/550ºC were observed by XRD. These changes are consistent with the hydration of Ca 2 SiO 4 to form different hydrated silicates (Garbev et al 2014;Mitsuda et al 1985;Roßkopf et al 2015;Speakman et al 1967;Yanagisawa et al 2006), being Ca 5 (SiO 4 ) 2 (OH) 2 the main compound identified in our samples (Criado et al 2015). Although these hydrated silicates only represent a small fraction of the total amount of silicates present in the composite material, the formation of these hydrates could play a role in the deterioration of the mechanical properties over cycling.…”
Section: Observations On the Decay Of Crushing Strengthsupporting
confidence: 90%
“…Other reflections are observed at angles close to 16, 32.3, 50 and 55 in 2. Similar observations have previously been reported in XRD studies of synthesized C-S-H and C-(A)-S-H systems (Taylor et al, 2010;Renaudin et al, 2009;Garbev et al, 2008). In C-S-H samples, it has been observed that the intensity of the main reflection at 29.5 2 increases with increasing Ca/Si ratio and there is a rightward shift of the peak to higher 2 angles.…”
Section: Direct Decomposition Of Hydrating Slagsupporting
confidence: 87%
“…In C-S-H samples, it has been observed that the intensity of the main reflection at 29.5 2 increases with increasing Ca/Si ratio and there is a rightward shift of the peak to higher 2 angles. The other reflection at 32.3 also increases with increasing Ca/Si ratio (Renaudin et al, 2009;Garbev et al, 2008). In C-(A)-S-H systems, incorporation of aluminium takes place by substitution of tetrahedral bridging sites of Si 4+ with Al 3+ .…”
Section: Direct Decomposition Of Hydrating Slagmentioning
confidence: 99%
“…This use has been very elegantly employed to follow the evolution of a single crystal (grain) of α-C 2 SH on heating. [136] The exact transformation mechanism of dehydration remained controversial but this work showed conclusive evidences of the formation of Dellaite at about 350°C. Figure 16 shows diffractionlimited IR images of a thin α-C 2 SH crystallite, thickness ≈ 3 µm, showing the spatially resolved intensity evolution with temperature of selected vibration bands to highlight the appearance and disappearance of the phases.…”
Section: Scanning Synchrotron Radiation Microscopiesmentioning
confidence: 76%